2022
DOI: 10.1039/d1ob02380b
|View full text |Cite
|
Sign up to set email alerts
|

Rh(iii)-Catalyzed ortho C–H functionalization of aromatic amides with bis(phenylsulfonyl)diazomethane and α-diazosulfones

Abstract: A Rh(III)-catalyzed migratory insertion of bis(phenylsulfonyl) carbene and -sulfonyl carbenes into ortho C−H bonds of aryl amides has been developed. The products were obtained with moderate to excellent yields under...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Based on our previous study, [9a] [Cp*RhCl 2 ] 2 /AgSbF 6 was examined, but only 7% yield was observed (Table 1, entry 2). While [Cp*RhCl 2 ] 2 /AgSbF 6 /AgOAc was used as the catalyst, [9b] to our delight, an excellent yield was obtained (Table 1, entry 3). Other transition metal catalysts (Ir, Pd, Co and Ru) were also examined (Table 1, entry 4), but they were found to be inefficient for the reaction.…”
Section: Resultsmentioning
confidence: 90%
“…Based on our previous study, [9a] [Cp*RhCl 2 ] 2 /AgSbF 6 was examined, but only 7% yield was observed (Table 1, entry 2). While [Cp*RhCl 2 ] 2 /AgSbF 6 /AgOAc was used as the catalyst, [9b] to our delight, an excellent yield was obtained (Table 1, entry 3). Other transition metal catalysts (Ir, Pd, Co and Ru) were also examined (Table 1, entry 4), but they were found to be inefficient for the reaction.…”
Section: Resultsmentioning
confidence: 90%
“…We initiated the study with a model reaction of N -nitrosoaniline 1a and diazonaphthoquinone 2a , and the results are summarized in Table 1. Referring to our previous studies, 9 [Cp*RhCl 2 ] 2 /AgSbF 6 was used as the catalyst in dichloroethane (DCE) (Table 1, entry 1). To our delight, the expected product 3a was obtained in 68% yield.…”
Section: Resultsmentioning
confidence: 99%